2008
DOI: 10.1007/s15010-008-7202-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Early Liver Fibrosis in Patients with Intestinal Schistosomiasis: Sonographic and Histologic Findings in Schistosoma mansoni Infection

Abstract: In our small study, US seemed to underestimate hidden liver fibrosis in intestinal schistosomiasis. In some European clinical settings, histological evaluation by liver biopsy may be a useful tool to detect early liver pathology in schistosomiasis mansoni. These findings could provide additional information for studies from endemic areas where US is commonly used for morbidity assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Thus an infected child could therefore wait up to 3–4 years before receiving first treatment, and with this may have already entered a more ‘chronic’ stage of disease [40], [41], [42], [43]. For example, earlier clinical and ultrasound studies in Uganda in children aged 6 and above, have shown significant hepatosplenomegaly (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus an infected child could therefore wait up to 3–4 years before receiving first treatment, and with this may have already entered a more ‘chronic’ stage of disease [40], [41], [42], [43]. For example, earlier clinical and ultrasound studies in Uganda in children aged 6 and above, have shown significant hepatosplenomegaly (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has, however, to be taken into account that early fibrotic liver changes are likely to be underestimated when only the characteristic macroscopically evident ultrasonographic features are taken into account (Kabatereine et al 1999;Richter 2000;Chiavaroli et al 2008). Non-specific abnormalities such as increase in predominantly left liver lobe size have been discussed as constituting an early sign of incipient hepatic involvement (DoehringSchwerdtfeger et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, liver fibrosis is generally evaluated by ultrasonography, which is a safe, rapid, noninvasive, and relatively inexpensive technique for assessing schistosomiasis-related lesions in individual patients and in community surveys [10,11], although histopathologic assessment of liver biopsy is generally regarded as being the "gold standard" of fibrosis evaluation [29]. There have been no previous studies that have made a direct comparison of S japonicum-induced fibrosis by ultrasound and liver biopsy pathology; and to our knowledge, this study is the largest study comparing the two methods of fibrosis assessment in advanced schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%